The Effect Of Live Streaming, Price And Promotion Of Tiktok Shop On Buying Interest In Preloved Consumers In Generation Z In Bengkulu City - Habibullah, Wahyu; Yulianti, Oni; Hanila, Siti (Universitas Dehasen Bengkulu, 2025)
The aim of this research is to find out whether live streaming, prices and promotions have an effect on buying interest of preloved consumers in generation Z in Bengkulu City. This type of research is quantitative. The data collection method in this research used a questionnaire technique, with a sample of 170 respondents. The research results show that multiple linear regression Y = 0.276 + 0.377 X1 + 0.311 X2 + 0.489 X3 + 0.994. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the variables Live Streaming (X1), Price (X2) Promotion (X3), the value is 0 (zero), on the Purchase Interest (Y) of Preloved Consumers in Generation Z in Bengkulu City. The results of the research show that the live streaming test (XI) shows tcount 2,782 > ttable 1,672 and significance 0.023 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that live streaming has a positive and significant effect on buying interest in preloved consumers in generation Z in Bengkulu City. The price test results (X2) show tcount 2.357 > ttable 1.672 and significance 0.021 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that price has a positive and significant effect on buying interest of preloved consumers in generation Z in Bengkulu City. The results of the promotion test (X3) show tcount 3.700 > ttable 1,672 and significance 0.000 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning promotion has a positive and significant effect on buying interest of preloved consumers in generation Z in Bengkulu City. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 36.690> 2.53, so it is concluded that accepting the hypothesis, meaning that there is a simultaneous influence between Live Streaming (X1), Price (X2) Promotion (X3) the value is 0 (zero), on Purchase Interest (Y) of Preloved Consumers in Generation Z in Bengkulu City. This can be seen at the significance level of 0.000 <0.05.